Development and Validation of a Capacity for Wonder Scale for Use in Educational Settings. (14th May 2020) - Geller, Gail; Steinman, Christopher; Caldwell, Meredith; Goldberg, Harry; Hanlon, Caitlin; Wonnell, Teresa; Merritt, Maria W.
Experiences of wonder should be valued, protected, and promoted in academic settings. Identification of learning environments and interventions that cultivate students' capacity for wonder (CfW) first requires a means to measure it. We used a mixed-methods approach to develop and validate a measure of CfW. In the qualitative component (Studies 1–3), we content analyzed open-ended descriptions of wonder (Study 1), interviewed people whom others identified as exemplifying CfW (Study 2), and conducted focus groups to review, for quality and consistency, and to establish face validity of, potential inventory items that capture wonder (Study 3). These items were then subjected to standard psychometric analyses in the quantitative component of our methods (Studies 4–6). In Study 4, exploratory factor analysis (EFA) revealed CfW may contain two subscales representing "Perspective Shifting" and "Emotional Reawakening." In Study 5, confirmatory factor analysis (CFA) corroborated this two-factor structure in an independent sample and longitudinally across 17 months, establishing a final 10-item CfW scale; In Study 6, we assessed the scale's discriminant and convergent validity. CfW was weakly to moderately correlated with theoretically related constructs of curiosity, tolerance for ambiguity, humility, and empathy. We conclude with a discussion of future directions and potential applications.